2018
DOI: 10.1093/abbs/gmy066
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes promote VEGF expression and alleviate ventilator-induced lung injury in mice

Abstract: Mechanical ventilation (MV) is an important procedure for the treatment of patients with acute lung injury or acute respiratory distress syndrome in a clinical setting; however, MV can lead to severe complications, including ventilator-induced lung injury (VILI). Telocytes (TCs) can promote tissue repair following injury in the heart, kidneys, and other organs. The aim of this study was to investigate the role of TCs in VILI in mice and the associated mechanisms. By using in vivo studies in mice and in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…VEGF increase the vascular permeability by the endothelial cells through increasing the fenestrations 78 . Both VEGF and PDGF Receptor-α are expressed by TCs 79,80 . In the current study, VEGF was also expressed by camel efferent ductule TCs.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF increase the vascular permeability by the endothelial cells through increasing the fenestrations 78 . Both VEGF and PDGF Receptor-α are expressed by TCs 79,80 . In the current study, VEGF was also expressed by camel efferent ductule TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Induced apoptosis in dermal keratinocytes can delay wound healing processes [22]. In our research, TCs non-contact co-culture reduced the LPS induced early, late and whole stages of apoptosis and cell death in HaCaT Recently study showed that cytokines, including VEGF and EGF, released by TCs are considered to be key factors were considered to be the mechanism for TCs promotion on angiogenesis [16,17].…”
Section: Discussionmentioning
confidence: 54%
“…As some groups described, TCs could secret many cytokines, including EGF and VEGF [16,17]. Since the proliferation of cells cocultured with TCs was altered, EGF was selected as the representative factor and being detected.…”
Section: Egf Mrna Level Was Increase In Tcs After Lps Stimulationmentioning
confidence: 99%
“…Also, TCs secretome factors could participate in decidua formation [17]. Some studies pointed to the angiogenic properties of TCs Telocytes: New Connecting Devices in the Stromal Space of Organs DOI: http://dx.doi.org /10.5772/intechopen.89383 due to vascular endothelial growth factor (VEGF) expression [15,82,83], while others indicated the anti-oxidative properties of TCs because the TCs specific morphology can be changed by modifying the redox balance of their environment or by aging due to their richness in SOD2 (mitochondrial superoxide dismutase) [21,84].…”
Section: Telocytes In Uterus and Fallopian Tubes In Healthy Conditionmentioning
confidence: 99%